Assibi A. Amidu 2009. Matrix Nominal Phrases in Kiswahili Bantu. A Study of their Effects on Argument Syntax. - Tiewa, Kathrin (AAeO - Afrikanistik-Aegyptologie-Online, 2010)
Assibi A. Amidu’s contribution is undoubtedly a highly challenging one to the direct study of the Kiswahili Bantu language. Aiming at complementing the existing grammars and monographs of living languages the author intends to illuminate some paradoxes of the Kiswahili syntax and morphology. Having defined this aim he presents a clearly structured monograph to the interested reader, consisting of six chapters, relating to one another.